Metal-Free [3+2] Oxidative Coupling of Phenols with Alkenes: Synthesis of Dihydrobenzofurans - Zhao, Yating; Huang, Binbin; Yang, Chao; Li, Bing; Xia, Wujiong (Synthesis, 2015)
Herein, we demonstrated a benign and metal-free [3+2]-cycloaddition reaction using simple and readily available phenols and styrenes as substrates and sodium persulfate as an inexpensive and environmentally friendly oxidant for the direct synthesis of dihydrobenzofurans. This methodology was applied to the synthesis of corsifuran A in a single step.
Keywords: metal-free; phenols; alkenes; sodium persulfate; dihydrobenzofuran